Shalat Sebagai Sarana Pemecah Masalah Kesehatan Mental (Psikologis) - Anisa Maya Umri Hayati (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2020)
Of the various religions in the world, Islam is the most special religion from other religions and is the religion most loved by Allah SWT. In Islam, there are many acts of worship that have the value of reward, whether it is worship that is obligatory or sunnah to be performed. Prayer is one of the many prayers in Islam that must be performed by Muslims who are shown to Allah SWT. By praying our hearts will always feel at ease and peaceful. Prayer means prayer or mercy. Prayer is said to be a prayer because the movements of the prayer all contain the meaning of prayer shown to Allah SWT. All the recitation of the prayer is a form of glorification of a servant to his Lord. The series of sayings and movements are not just words and movements without meaning or meaning, but each contains a lot of history, philosophy, ibrah, goals, and wisdom for those who practice it. Apart from compulsory worship, prayer also has many benefits, one of which is psychological or mental health. The psychological aspect itself is a feeling that arises from within our heart or soul. From a psychological aspect, one of the benefits obtained is a peaceful soul. Prayers make our souls more peaceful and peaceful. Besides that, prayer can also reduce excessive stress. Prayer makes a Muslim feel calmer in heart, clean in spirit, and in balance. Prayers can also be used as spiritual therapy for healing patients. In Islam, prayer as a form of worship is the most prudent and prioritized because it has a very, very important position in a person's life, especially Muslims and in the pillars of Islam ranks second after the creed